Implementasi Pengelolaan Alokasi Dana Desa pada Masa Pandemi Covid-19 - Sandra Hartati; Rigel Nurul Fathah (Universitas Muhammadiyah Jakarta, 2022)
This study aims to analyze the management of village fund allocation and the effectiveness of financial performance in South Pringgasela Village which has received budget reductions during the Covid-19 pandemic. This study employs descriptive qualitative methods through interviews, observation and documentation. The results show that the management of village fund allocation in South Pringgasela Village technically and administratively has been carried out well based on the timeliness of disbursement of village funds allocation, and the effectiveness level of financial performance by 92% indicates that the financial performance is effective based on the achievement of goals, timeliness, suitability benefits, and expectations of society.